Forward to the past: Short-term effects of the rent freeze in Berlin - Anja M. Hahn; Konstantin A. Kholodilin; Sofie Waltl; Marco Fongoni (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
In 2020, Berlin introduced a rigorous rent-control policy responding to soaring rents by setting a cap on rental prices: the Mietendeckel (rent freeze). The policy was revoked one year later by the German Constitutional Court. Although successful in reducing rents during its duration, the consequences for Berlin's rental market and adjacent municipalities are not clear. In this paper we evaluate the short-term causal effect of the rent freeze on the supply-side of the market, both in terms of prices and quantities. We develop a theoretical framework capturing the key features of the rent freeze, and test its predictions using a rich pool of detailed rent adverts. In addition, we estimate hedonic-style Difference-in-Differences and Spatial Regression Discontinuity models comparing price trajectories of dwellings inside and outside the policy's scope. Advertised rents drop significantly upon the policy's enactment. A substantial rent gap across the administrative border emerges, with rapidly growing rents for Berlin's (unregulated) adjacent municipalities. Moreover, we document a significant drop in the number of advertised properties for rent, a share of which appears to be permanently lost for the rental sector.
Keywords: C14; C43; O18; D04; 330; First-Generation Rent Control; Rent Freeze; Urban Policy; Local Political Economy; Supply Disruptions; Legal Uncertainty; Berlin